Mantle cell lymphoma management trends and novel agents: where are we going?. (February 2022) - Pu, Jeffrey J.; Savani, Malvi; Huang, Nick; Epner, Elliot M.
The heterogeneity in disease pathology, the unpredictability in disease prognosis, and the variability in response to therapy make mantle cell lymphoma (MCL) a focus of novel therapeutic development. MCL is characterized by dysregulated expression of cyclin D1 through a chromosome t (11;14) translocation. MCL international prognostic index (MIPI), ki-67 proliferation index, and TP53 mutation status are currently utilized for prognostication. With advances in pharmacokinetic analysis and drug discovery, treatment strategy has evolved from chemotherapy to combination of targeted, epigenetic, and immune therapies. In this review, we discuss investigational and newly approved treatment approaches. In a short time, the US Food and Drug Administration (FDA) has approved five agents for the treatment of MCL: lenalidomide, an immunomodulatory agent; bortezomib, a proteasome inhibitor; and ibrutinib, acalabrutinib, and zanubrutinib, all Bruton kinase inhibitors. Epigenetic agents (e.g. cladribine and vorinostat), mammalian target of rapamycin (mTOR) inhibitors (e.g. temsirolimus and everolimus), and monoclonal antibodies and/or antibody-drug conjugates (e.g. obinutuzumab, polatuzumab, and ublituximab) are promising therapeutic agents currently under clinical trial investigation. Most recently, chimeric antigen receptor (CAR)-T cell therapy and bispecific T-cell engager (BiTE) therapy even open a new venue for MCL treatment. However, due to its intricate pathology nature and high relapse incidence, there are still unmet needs in developing optimal therapeutic strategies for both frontline and relapsed/refractory settings. The ultimate goal is to develop innovative personalized combination therapy approaches for the purpose of delivering precision medicine to cure this disease.